Barron's GRE: Graduate Record Examination (Barron's: The Leader in Test Preparation) - Weiner Green, Sharon (Barron's Educational Series, 2017)
The 18th edition of Barron's GRE test preparation manual offers prospective graduate students intensive preparation for the Graduate Record Exam, as it is currently administered. Although question types on the GRE are scheduled to change substantially beginning August 1, 2011, students who opt to take the test before August 1, will find the help they're looking for in this edition. They will want to use Barron's GRE, 18th edition, as their test prep tool. Opening chapters of the 18th edition provide a perspective on the current exam with a GRE overview, advice on effective test-taking tactics, and a diagnostic test to help students pinpoint their strengths and weaknesses. Subsequent chapters review all GRE test areas and include practice exercises for the following topics: antonym, analogy, and sentence-completion questions, reading comprehension, vocabulary, analytical writing, discrete quantitative questions, quantitative comparison questions, data interpret